2017
DOI: 10.1111/sed.12419
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate and silicate biomineralization in a hypersaline microbial mat (Mesaieed sabkha, Qatar): Roles of bacteria, extracellular polymeric substances and viruses

Abstract: In a modern peritidal microbial mat from Qatar, both biomediated carbonates and Mg‐rich clay minerals (palygorskite) were identified. The mat, ca 5 cm thick, shows a clear lamination reflecting different microbial communities. The initial precipitates within the top millimetres of the mat are composed of Ca–Mg–Si–Al–S amorphous nanoparticles (few tens of nanometres) that replace the ultrastructure of extracellular polymeric substances. The extracellular polymeric substances are enriched in the same cations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 133 publications
(189 reference statements)
6
104
0
Order By: Relevance
“…; Perri et al . ). The limitation in Ca 2+ supply can be a reason of the specific sequence of Mg–Si–Ca precipitation in Petukhovskoe soda lake stromatolites.…”
Section: Discussionmentioning
confidence: 97%
“…; Perri et al . ). The limitation in Ca 2+ supply can be a reason of the specific sequence of Mg–Si–Ca precipitation in Petukhovskoe soda lake stromatolites.…”
Section: Discussionmentioning
confidence: 97%
“…When Ca 2+ access to intracellular space, the existence of capsid synthetized by viral DNA provides nucleation site for initial calcification (Fig 10). This heterogeneous calcification involves addition of material to the preexisting viral surface, which may similar to mineralized virus in microbial mat from hot spring (Peng et al, 2013) or hypersaline lakes (Pacton et al, 2014;De Wit et al, 2015;Perri et al, 2017). The pathway that viral induced calcification during the lysis of the 15 host cells retrieved by experimental study expands roles of viruses in marine carbonate precipitation.…”
Section: +mentioning
confidence: 94%
“…10). 5 Preliminary investigations have also demonstrated that viruses from the hypersaline lake occur and are incorporated in biogenic carbonate, suggesting that virus may be mistaken for nanobacteria and play a role in initiating mineralization (De Wit et al, 2015;Pacton et al, 2014;Perri et al, 2017). The viral drive during the biogenic carbonate precipitation in hypersaline lakes is attributed to either an indirect route, involving silicified viruses as an intermediate phase during diagenesis (Pacton et al, 2014) or a direct incorporation of amino acids polymerized with viral proteins into growing high-Mg calcite crystals (De 10 Wit et al, 2015).…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations